The communication of difficult news about the approach applied to oncology: a bibliometric review (Research, Society and Development, 2020)
This study aims to identify and analyze the scientific knowledge produced about communicating bad news in oncology considering the national and international context. This is a bibliometric review of the scientific productions published in the five-year time cut in the LILACS, MEDLINE and CINAHL databases. The following steps were delimited: formulation of the problem and search procedures; data evaluation; data analysis and interpretation; and presentation of the review. Bibliometric analysis was performed to characterize the studies from the own creation form, facilitating reading, identification of relevant data from the literature, as well as data analysis. The research resulted in 49 works in the search of scientific productions. A detailed reading of the abstracts refinement of the scientific productions was carried out, where 129 studies were discarded because they are not in compliance with the inclusion criteria and 18 scientific productions were repeated in the databases. The mapping of scientific productions shows the importance of developing national and international studies in difficult news as one of the advanced practices involved in oncologic patient care.